IMPLEMENTASI PENDIDIKAN AGAMA HINDU BERBASIS GLOBAL - Ni Wayan Sukerti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The sacred teachings of the Vedas and Hindu literature view children or sons as the center of attention and activities related to education. Hindus in Bali believe that the character of a child is also determined by both parents, the environment and ceremonies related to the birth of a child. When a child is born, a person's character can be seen on the day of his birth called Daúavara (hari yang sepuluh), yaitu: “pandita, pati, sukha, duhkha, lara, manuh, mànusa, ràja, deva, dan raksasa”